ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH PADA KEBIJAKAN UTANG DI PERUSAHAAN FOOD AND BEVERAGE YANG TERCATAT DI BURSA EFEK INDONESIA - Gestiarfina, Jeni Elsa; Suryandani, Wulan (Bisnis-Net, 2024)
Debt policy is a company's strategy in using external funding to finance operational activities and increase revenue. If a company is unable to pay its debts, it will experience bankruptcy, so management must be able to make the right decisions in order to minimize the risk of bankruptcy that will be borne by the company. The purpose of this study was to see the effect of company size, profitability and liquidity on debt policy in food and beverage companies listed on the IDX in 2018-2022. This study uses purposive sampling technique so as to get a sample of 60 data on food and beverage companies listed on the IDX. The analysis technique used is multiple linear regression using SPSS 23. The results of this study indicate that company size has a significant positive effect on debt policy, profitability has a positive and insignificant effect on debt policy, while liquidity has a negative and insignificant effect on debt policy.